39 Molecular mechanisms of VEGFR inhibition-induced endothelial cell damage. (17th November 2015) - Rios, F; Montezano, AC; Van Der Mey, L; Small, H; Savoia, C; Touyz, RM
Abstract : VEGF/VEGFR inhibitors, used as anti-angiogenic drugs to treat cancer, induce severe hypertension. Molecular mechanisms are unclear, but nitric oxide (NO) and oxidative stress may be involved. We questioned whether reactive oxygen species (ROS) and Ang II also play a role in VEGF inhibitor-induced vascular dysfunction. Human microvascular endothelial cells (HMECs) were stimulated with vatalanib (VAT-VEGFR inhibitor) and gefitinib (GEF-EGFR inhibitor) in the absence/presence of Ang II. Activation of eNOS and MAPKs were assessed by immunoblotting. Antioxidant enzyme mRNA was analysed by qPCR. Endothelial microparticles, biomarkers of endothelial damage, tend to increase in subjects treated with VEGFR inhibitors. Phosphorylation of eNOS (28.3% ± 7.1) was decreased by VAT (p < 0.05). VAT decreased mRNA expression of Nox4 (0.5 ± 0.2) and H2 O2 -regulating antioxidants enzymes such as catalase (0.4 ± 0.1) and glutathione peroxidase (0.4 ± 0.1), while increased mRNA levels of Nox5 (3.35 ± 1.1) (p < 0.05 vs. veh). Ang II stimulation increased eNOS (171.2% ± 17.4) and ERK1/2 (177.5% ± 38.5) activation (p < 0.05); all effects were blocked only by GEF. Inhibition of VEGFR also blocked Ang II effects on SOD1 (1.33 ± 0.1), HO-1 (1.6 ± 0.3) and NQO1 (1.6 ± 0.3) mRNA levels (p < 0.05). In addition, Ang II increased Nox4 mRNA expression through VEGFR-dependent mechanisms. Ang II effects on eNOS phosphorylation were inhibited by PD123319 (AT2R antagonist) but not by losartan (AT1R antagonist). In conclusion, our data identify novel mechanisms whereby AngII, possibly through AT2R-dependent VEGFR transactivation, regulates eNOS activation, MAPK signalling and H2 O2 -related antioxidant enzymes.